Nucleic Acid Sensors and Type I Interferon Production in Systemic Lupus Erythematosus - Shrivastav, Meena; Niewold, Timothy B. (Frontiers in Immunology, 2013)
The characteristic serologic feature of systemic lupus erythematosus (SLE) is autoantibodies against one’s own nucleic acid or nucleic acid-binding proteins - DNA and RNA-binding nuclear proteins. Circulating autoantibodies can deposit in the tissue, causing inflammation and production of cytokines such as type 1 interferon. Investigations in human patients and animal models have implicated environmental as well as genetic factors in the biology of the SLE autoimmune response. Viral/Bacterial nucleic acid is a potent stimulant of innate immunity by both toll-like receptor (TLR) and non-TLR signaling cascades. Additionally, foreign DNA may act as an immunogen to drive an antigen-specific antibody response. Self nucleic acid is normally restricted to the nucleus or the mitochondria, away from the DNA/RNA sensors, and mechanisms exist to differentiate between foreign and self nucleic acid. In normal immunity, a diverse range of DNA and RNA sensors in different cell types form a dynamic and integrated molecular network to prevent viral infection. In SLE, pathologic activation of these sensors occurs via immune complexes consisting of autoantibodies bound to DNA or to nucleic acid-protein complexes. In this review, we will discuss recent studies outlining how mismanaged nucleic acid sensing networks promote autoimmunity and result in the overproduction of type I interferon. This information is critical for improving therapeutic strategies for SLE disease.